High Performance Application-Oriented Operating Systems - the EPOS Approach - Fröhlich, Antonio Augusto; Schröeder-Preikschat, Wolfgang (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.1999.19765, 1999)
This paper presents the EPOS approach to bring object-oriented operating systems closer to high performance parallel applications. The gap between them originates from the complexity of assembling an operating system out of a complex collection of complex classes. EPOS aims to deliver, whenever possible automatically, a customized runtime support system for each application. In order to achieve this, EPOS introduces the concepts of scenario-independent system abstractions, scenario adapters and inflated interfaces. An application designed and implemented following the guidelines behind these concepts can be submitted to a tool that will proceed syntactical and data flow analysis to extract a blueprint for the operating system. This blueprint is then refined by dependency analysis against information about the execution scenario acquired from the user via visual tools. The outcome of this process is a set of selective realize keys that will support the generation of the application-oriented operating system.